Village Head Term Extension In Indonesia: A Fiqh Siyāsah Dustūriyyah Perspective - Ilham Manando; Mohammad Yasir Fauzi; M. Dani Fariz Amrullah D (UIN Syekh Ali Hasan Ahmad Addary Padangsidimpuan, 2026)
The amendment to Article 39 paragraph (1) of Law Number 3 of 2024, which extends the term of office of village heads from six to eight years, raises questions about development continuity, limitations on power, and the welfare of village communities. This study aims to analyze the legal construction of the extension and assess its conformity with fiqh siyāsah dustūriyyah. This prescriptive-analytical normative legal research applies statutory, conceptual, and case approaches. Primary legal materials consist of Law Number 6 of 2014 as amended by Law Number 3 of 2024, Government Regulation Number 16 of 2026, and Constitutional Court Decisions Number 42/PUU-XIX/2021 and Number 92/PUU-XXII/2024; secondary legal materials consist of books and journal articles on village governance, democracy, accountability, and fiqh siyāsah. Legal materials were collected through document study and source tracing based on relevance, authority, recency, and traceability. They were analyzed through grammatical, systematic, and teleological interpretation, then tested against the principles of amānah, justice, shūrā, maṣlaḥah, accountability, and prevention of mafsadah. The study finds that the shift from six years for a maximum of three terms to eight years for a maximum of two terms reduces maximum cumulative tenure from eighteen to sixteen years but lengthens the interval of electoral accountability. The policy is therefore a conditional maṣlaḥah: its substantive legitimacy depends on effective BPD oversight, periodic performance evaluation, budget transparency, community participation, complaint mechanisms, and enforceable sanctions. These findings formulate a conditional maṣlaḥah test for distinguishing beneficial political stability from a concentration of village power